SULFATE MINERALIZATION IN A TUNNEL OF THE PYATIGORSKY PROVAL CAVE, NORTH CAUCASUS - O.Ya. Chervyatsova; A.V. Kasatkin; N.V. Chukanov; F. Nestola (Минералогия)
The paper reports on the results of studies of supergene sulfate mineralization found in a tunnel of the Pyatigorskiy Proval cave. The sulfate minerals include humberstonite K3Na7Mg2(SO4 )6(NO3 )2 •6H2O, sideronatrite Na2 Fe(SO4)2(OH)•3H2O, metasideronatrite Na2 Fe(SO4)2(OH)•H2 O, natrojarosite NaFe3(SO4)2(OH)6 , tamarugite NaAl(SO4)2 •6H2O, and epsomite MgSO4 •7H2O, which were identified by electron probe microanalysis, powder X-ray diffraction and infrared spectroscopy. The presence sulfate sulfur can be related to both the oxidation of sulfide grains, which were found in some samples, and the oxidation of gaseous H2S air oxygen. Humberstonite and metasideronatrite are found for the first time in Russia.